2008
DOI: 10.1590/s1413-86702008000400010
|View full text |Cite
|
Sign up to set email alerts
|

Occult B infection in the Brazilian northeastern region: a preliminary report

Abstract: A sentinel study on viral hepatitis is currently being carried out in the village of Cavunge in a semiarid rural region of the state of Bahia, northeastern Brazil. This study has identified individuals in whom anti-HBc IgG was the only serological marker for hepatitis B virus (HBV). This serological pattern may constitute evidence of occult HBV infection. This study Investigated the possibility of occult hepatitis B virus infection in individuals in a rural community who tested positive for anti-HBc IgG alone.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(23 reference statements)
0
2
1
2
Order By: Relevance
“…This goes against some studies that indicate greater prevalence among men 17,19 and other studies that show a higher caseload among women 22 . It is the view of the researchers, however, that men are probably more exposed to sources of infection due to behavioral aspects such as drug use, promiscuity, infrequent prophylactic use, greater frequency of travel outside of the indigenous areas, and decorative body piercings.…”
Section: Ethical Considerationscontrasting
confidence: 58%
See 1 more Smart Citation
“…This goes against some studies that indicate greater prevalence among men 17,19 and other studies that show a higher caseload among women 22 . It is the view of the researchers, however, that men are probably more exposed to sources of infection due to behavioral aspects such as drug use, promiscuity, infrequent prophylactic use, greater frequency of travel outside of the indigenous areas, and decorative body piercings.…”
Section: Ethical Considerationscontrasting
confidence: 58%
“…Barros-Junior et al 18 reported a lower prevalence in 51 (17.6%) patients of the Brazilian Amazon. In studies conducted in the States of Bahia and Mato Grosso do Sul the prevalence was 18% and 24.7% 19,20 , respectively, showing that HBV-DNA prevalence is quite heterogeneous in Brazil.…”
Section: Ethical Considerationsmentioning
confidence: 98%
“…For example, Minuk et al reported that HBV-DNA was detected in 14/487 (2.87%) Inuit people (Canada) [42]. Brazilian investigators showed that 2 of 1536 (0.13%) blood donors were infected with OBI [43]. Interestingly, Gutierrez et al from Venezuela revealed that no OBI cases were found in 2,075 screened blood samples [44].…”
Section: Americanmentioning
confidence: 99%
“…La resolución del HBsAg indica generalmente seroconversión al anticuerpo contra el antígeno de superficie del VHB (anti-HBs) y la consecuente remisión de la infección por el VHB (14), es importante determinar el nivel de anti-HBs en IU/L, para establecer la infectividad, títulos mayores de 100 IU/L indican generalmente que el individuo no es infectante (15).…”
unclassified
“…Así mismo, pueden presentarse individuos en los que el anti-HBc de tipo IgG (anti-HBcIgG) es el único marcador de memoria positivo: resultados falso-positivos, pacientes que tuvieron la infección y se resolvió, pacientes que no han generado títulos de anti-HBs, pacientes con infección con el VHB que no presentan reactividad en el HBsAg, debido a la mutación del gen S, o en casos de replicación viral muy baja (14).…”
unclassified